Analysis of pneumothorax recurrence risk factors in 843 patients who underwent videothoracoscopy for primary spontaneous pneumothorax: results of a multicentric study. (30th April 2020) - Cattoni, Maria; Rotolo, Nicola; Mastromarino, Maria Giovanna; Cardillo, Giuseppe; Nosotti, Mario; Mendogni, Paolo; Rizzi, Alessandro; Raveglia, Federico; Siciliani, Alessandra; Rendina, Erino A; Cagini, Lucio; Matricardi, Alberto; et al.
Abstract: OBJECTIVES: Risk factors for pneumothorax recurrence after videothoracoscopy for primary spontaneous pneumothorax are still being debated. The goal of this study was to assess whether the pleurodesis technique and other variables are possibly associated with the postoperative ipsilateral recurrence of pneumothorax. METHODS: We retrospectively collected data of 1178 consecutive ≤40-year-old patients who underwent videothoracoscopy for primary spontaneous pneumothorax in 9 centres between 2007 and 2017. We excluded patients with hybrid pleurodesis and/or incomplete follow-up, leaving for analysis 843 cases [80% men; median age (interquartile range) 22 (18–28) years]. Univariable and multivariable analyses were performed by logistic regression and tested by Cox regression model to assess factors related to ipsilateral pneumothorax recurrence including age, gender, body mass index, smoking habit, cannabis smoking, respiratory comorbidity, dystrophic severity score, surgical indication, videothoracoscopy port number and side, lung resection, pleurodesis technique and postoperative prolonged air leak (>5 days). RESULTS: Blebs/bullae resection was performed in 664 (79%) patients. Pleurodesis was achieved by partial pleurectomy in 228 (27%) cases; by pleural electrocauterization in 176 (21%); by pleural abrasion in 121 (14%); and by talc poudrage in 318 (38%). During a median follow-up period of 70.0 months (95% confidence interval 66.6–73.4), pneumothorax recurred in 79 patients (9.4%); among these, 29 underwent redo surgery; 34, chest drain/talc slurry; and 16, clinicoradiological observation. The only independent risk factor for recurrence was postoperative prolonged air leak ( P < 0.001) that was significantly related to blebs/bullae resection ( P = 0.03). CONCLUSIONS: In this multicentric series, postoperative ipsilateral pneumothorax recurrence was remarkable and independently related to prolonged postoperative air leak; besides the retrospective study setting, the pleurodesis method did not have an impact on recurrence. To prevent prolonged air leak, blebs/bullae treatment should be accurate and performed only if indicated.